Expression Study of Banana Pathogenic Resistance Genes - Fenny M. Dwivany; Rizkita Rahmi Esyanti; Aksarani 'Sa Pratiwi; Herafi Zaskia (Bogor Agricultural University, Indonesia, 2016)
Banana is one of the world's most important trade commodities. However, infection of banana pathogenic fungi (Fusarium oxysporum race 4) is one of the major causes of decreasing production in Indonesia. Genetic engineering has become an alternative way to control this problem by isolating genes that involved in plant defense mechanism against pathogens. Two of the important genes are API5 and ChiI1, each gene encodes apoptosisinhibitory protein and chitinase enzymes. The purpose of this study was to study the expression of API5 and ChiI1 genes as candidate pathogenic resistance genes. The amplified fragments were then cloned, sequenced, and confirmed with in silico studies. Based on sequence analysis, it is showed that partial API5 gene has putative transactivationdomain and ChiI1 has 9 chitinase family GH19 protein motifs. Data obtained from this study will contribute in banana genetic improvement.